(untitled) (Global Journal of Medical Research, 2021)
Background: Currently, pap smears are used to screen cervical cancers in Sri Lanka. Two major drawbacks of pap smear screening method are the suboptimal sensitivity and the low coverage. HPV/DNA screening method can be used as a cervical cancer screening method and high sensitivity (92.9%) is the major advantage of it. Specimens can be collected for HPV/DNA test from two sampling site a) from the cervix b) from the vagina. Vaginal specimen collection is more feasible as it does not require speculum examination, therefore primary healthcare worker can be collected a specimen. The objective of the study is to compare HPV/DNA test results of specimens from two sampling sites as a measure to improve the quality and coverage of the National Cervical Cancer Screening programme in Sri Lanka.